Drug utilization in selected health facilities of South West Shoa Zone, Oromia Region, Ethiopia - Kebede, Mengistu (Drug Healthc Patient Saf, 2015)
BACKGROUND: Sustaining the availability and rational use of safe and effective drugs is a major problem in developing countries. Irrational drug use affects quality of health care more than accessibility of drugs. OBJECTIVE: To assess drug utilization in selected health facilities of South West Shoa Zone, Oromia Region, Ethiopia. METHODS: A cross-sectional study was conducted in selected health facilities of South West Shoa Zone from January 21–28, 2012 by using structured questionnaires. RESULTS: Of 50 prescribers and 30 dispensers, 58% and 83.3% were males, respectively. The result showed that majority of prescribers agreed on availability of essential drugs (72%) and had access to up-to-date drug information (76%). However, 43.3% of dispensers didn’t get access to up-to-date drug information. 86% and 88% of prescribers note cost of drugs and stick to standard treatment guidelines of Ethiopia during prescription, respectively. All drug dispensers check the name of the drug (100%), age of the patient (90%), the dosage form of drug (96.7%), the route of administration (90%), the duration of therapy (86.7%), and frequency of administration (86.7%) for prescription papers. CONCLUSION: In general, drug utilization at the study sites was found to be good, although there are major deviations from the concept of rational drug use.